MicroRNA-379 Modulates Prostate-Specific Antigen Expression Through Targeting the Androgen Receptor in Prostate Cancer - Cassidy, James R; Persson, Margareta; Voss, Gjendine ; 0000-0002-0097-517X; Underbjerg, Kira Rosenkilde; Ivkovic, Tina Catela; Bjartell, Anders; Edsjö, Anders; Lilja, Hans ; 0000-0001-5871-7846; Ceder, Yvonne ; 0000-0002-8705-8293 (Cancers, 2025)
Background: MicroRNA-379 (miR-379) has been reported to play a tumour-suppressing role in several cancer types. Our previous work demonstrated that miR-379 overexpression attenuates the metastatic spread of prostate cancer (PCa) both in vitro and in vivo. However, the underlying mechanisms remain poorly understood. Methods: To elucidate the mechanisms by which miR-379 affects metastases, we performed a cytokine array to identify secreted proteins modulated by miR-379 dysregulation in a bone microenvironment model. We then assessed the levels of the key candidate, and performed functional studies, including reporter assays, of the transcriptional regulation. Results: Prostate-specific antigen (PSA)-the clinically widely used blood biomarker for PCa-emerged as the most significantly affected secreted protein. We observed that PSA secretion increased following miR-379 inhibition and decreased with miR-379 overexpression, with parallel changes in intracellular PSA levels. However, our data suggests that miR-379 does not directly regulate PSA expression. Instead, miR-379 appears to downregulate androgen receptor (AR) expression by targeting its 3'-untranslated region (3'-UTR), thereby indirectly reducing PSA transcription through diminished AR-mediated promoter activation. Supporting this indirect mechanism, analysis of clinical samples from prostate cancer patients revealed an inverse correlation between expression of miR-379 in prostatic tissue and serum PSA levels. Furthermore, reduced miR-379 expression was associated with increased levels of AR immunostaining in malignant tissues. Conclusions: Taken together, these findings suggest that miR-379 negatively regulates PSA secretion indirectly via suppression of AR, and that the interplay between miR-379, AR, and PSA may contribute to the metastatic progression of PCa to bone.